Pharmacological activity of subcritical CO2 extract of Plantago major - Alimova, U.; Ustenova, G.; Kozhanova, K.; Zhandabayeva, M.; Kantureyeva, A.; Mombekov, S.; Mukanova, A.; Alimzhanova, M.; Yudina, Y.; Hrubnyk, I.; Maloshtan, L.; Botabayeva, R. (Regulatory Mechanisms in Biosystems, 2025)
This study comprehensively investigates the anti-inflammatory, wound-healing, and toxicological properties of Pla n tago major CO 2 extract using a series of in vivo experimental models in rats and mice. The anti-inflammatory activity was assessed in two models of acute inflammation. In the carrageenan-induced paw edema model, which reflects prostagla n din-mediated inflammation, the extract demonstrated a dose-dependent effect. At the highest dose of 50 mg/kg, paw swe l ling was reduced by up to 43% during peak inflammation, though the effect remained inferior to that of the reference drug, sodium diclofenac. In the zymosan-induced paw edema model, which mimics leukotriene-driven inflammation via the lipoxygenase pathway, the extract at a dose of 50 mg/kg significantly inhibited edema formation throughout the exper i ment and showed comparable efficacy to quercetin, suggesting potential lipoxygenase inhibition. The reparative effects of the extract were examined in a linear skin incision model. Administration of the extract at 50 mg/kg significantly increased the tensile strength of the wound (578.4 ± 4.2 vs. 416.6 ± 6.0 g in the control group), accelerated granulation tissue form a tion, and normalized serum protein levels, indicating improved wound healing capacity. In acute toxicity studies, no signs of behavioral abnormalities or mortality were observed in rats or mice following a single oral dose of up to 5000 mg/kg. According to standard toxicological classifications, the extract can be considered practically non-toxic. Taken together, the results indicate that P. major CO 2 extract possesses moderate but stable anti-inflammatory activity, notable wound-healing potential, and excellent safety. These findings support the further pharmacological development of the extract and hig h light its promise as a plant-derived therapeutic agent for treating inflammatory conditions and promoting tissue repair.